إشراك الجمعيات أحد الوسائل القانونية في حماية البيئة - كرمي, ريمة (University of Eloued جامعة الوادي, 2017)
يواجه العالم منذ بضعة عقود، موقفا صعبا لم يسبق له مواجهته، حيث تعاني الطبيعة على كوكب الأرض من التدهور بفعل النشاطات الإنسانية المتعاظمة، ما أدى إلى انشغال جميع الدول بقضية حماية البيئة وعقدت من اجلها الكثير من الاتفاقيات الدولية. تتطلب عملية حماية البيئة مجهودات وطنية وأخرى دولية، فالمجهودات المحلية هي جزء لا يتجزأ من المجهودات الدولية لحماية البيئة. فمؤسسات المجتمع المدني-المهتمة بالبيئة-مطالبة اليوم بوضع السياسات التي تساهم في الحد من التلوث بمختلف أنواعه، خاصة بعد ما اعترف لها بدور الشريك للإدارة في تحقيق أهداف الإستراتيجية الوطنية لحماية البيئة، و قد نظم القانون رقم 03-10 فصل خاص بها. Abstract: A few decades ago, the world is facing a difficult situation, has never faced, where nature is suffering from degradation due to human activities, leading to the concern of all States to the cause of protection the environment, it has grow into the large number of international conventions, environmental protection processes and other national and international initiatives require the protection of the environment,. The institutions of civil society develop policies that contribute to the reduction of pollution in all its forms, especially after admitting his role of director associated with the objectives of the national strategy for environmental protection in the name of law No. 03-10 corresponding to the protection of the environment in the context of sustainable development
Engaging associations is one of the legal means to protect the environment
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: البيئة- الجمعيات- القانون- الحماية; Environment - Associations - Law - Protection